Seeing as One? - Jenny Maria Lundgaard (Nordic Journal of Science and Technology Studies)
From 2019, a one-year trial tested the use of drone technologies within the Norwegian Police Services. Drones, designed to facilitate the collection, storage, and dissemination of live film and images, were implemented with the expectation that shared visual data would enhance situational awareness and thus improve police practices. This study, based on ethnographic data collected during the trial period, examines how these new technological tools shape the practices of professional vision. It explores the relationship between seeing and knowing by looking at how drone technologies influence ‘the police gaze’ (Finstad, 2000), police officers’ collection and processing of their visual surroundings. As the human gaze merges with the drone gaze, visual data is produced and can be distributed in larger police operations. Drones were intended to simplify team decision-making by  providing images considered true and certain, thus reducing the need for oral radio communication. However, paradoxically, one outcome of the trial was the creation of an observation manual for improving the oral conveying of drone-collected information. The findings underscore the complexities of police knowledge production, illustrating the intricate interactions between human and non-human agents in operational policing. While drones materialize and spread the police gaze, merely sharing images does not ensure a shared understanding of an incident or operation. Establishing mutual comprehension of incidents or operations remains a nuanced and delicate process.